Potential of morpho-physiological traits for identification of drought tolerant bread wheat (Triticum aestivum L.) genotypes under moisture stress and irrigated environment - Manilal, Patel Jashvantlal; Patel, Shashikant Kacharabhai; Patel, Chirag Rameshbhai; Patel, Amrutbhai Shankerlal; Pachchigar, karen p (Journal of Cereal Research, 2020)
An experiment was performed to evaluate the effects of drought stress on yield, plant architecture and physiological traits in bread wheat genotypes.Â  Field experiment was conducted with twenty genotypes at wheat research station, Vijapur, under normal and drought conditions for two years in crop season rabi 2017-18 and 2018-19 using randomized complete block design replicated twice at each environment. Grain yield and its attributes were recorded at Zadoks dcimal scale 9, phenological traits at scale 6, plant architecture at scale 2 and 9 and physiological traits were measured 2, 6 and 7 Zadoks decimal scale. Significant differences for all the traits studied were found among genotypes both under normal and moisture stress conditions. For yield related traits, minimum reduction was noticed for harvest index during both the crop seasons (0.63 % and 1.88 %). The values of canopy temperature was higher in stress conditions in both the crop seasons, in post anthesis stage, higher temperature in second crop cycle (-33.93%) was observed. Among the whole panel genotypes DBW 154 and GW 510 performed well under drought stress with higher yield and harvest index. Â Among the tested genotypes, GW 451, DBW 154 and GW 508 were the coolest genotypes at post anthesis (CT II) but failed to maintain the grain yield under drought stress. Based on higher values of stress tolerance index, genotypes DBW 154, VL 1004, GW 510 and GW 512 were classified as drought tolerant genotypes which could be utilised in wheat improvement programme aimed at drought tolerance.